A disposable electrode modified with metal orthovanadate and sulfur-reduced graphene oxide for electrochemical detection of anti-rheumatic drug. (13th October 2021) - Rajaji, Umamaheswari; Arya Nair, J. S.; Chen, Shen-Ming; Sandhya, K. Y.; Alshgari, Razan A.; Jiang, Ting-Yu
Abstract : CVO@SRG composite was prepared by a hydrothermal method and the voltammetric measurement of an organic compound. Abstract : A cerium vanadium oxide decorated sulfur doped-reduced graphene oxide (CVO@SRG) nanocomposite was prepared by a modest hydrothermal method and investigated for the voltammetric measurement of an organic compound, sulfasalazine (SSZ), which has been selected for its importance as a pharmaceutical product. The as-synthesized CVO@SRG was characterized by electron microscopy and spectroscopy analyses for its structure and formation. A CVO@SRG modified disposable screen-printed carbon electrode (SPCE) as an electrocatalytic SSZ sensor exhibited an improved oxidation current at a lower oxidation potential compared to the unmodified electrode and SRG/SPCE. Under optimum conditions, the electrochemical studies of CVO@SRG/SPCE revealed a wide linear range from 0.005 to 284.6 μM with a lower limit of detection in the nanomolar range (1.2 nM) and a higher sensitivity (90.55 μA μM −1 cm −2 ) towards SSZ. The critical practicability of the newly made sensor was examined, and it demonstrated admirable selectivity, repeatability, and reproducibility. Furthermore, the sensor was used to sense SSZ in both serum and urine samples, which proves the potential of CVO@SRG/SPCE for practical applicability.